[Rezension von: Meier, John P., 1942-, A marginal Jew. Rethinking the historical Jesus. Vol. 4: Law and love] - Dunn, James D. G. (The journal of theological studies, 2013)
The William K. Warren Professor of Theology (New Testament) at the University of Notre Dame has already given us three hefty volumes on his quest for A Marginal Jew. Volume 1, The Roots of the Problem and the Person, appeared as long ago as 1991 (a mere 484 pages). Volume 2: Mentor, Message and Miracle took only another three years (1994), but ran to 1,118 pages. Volume 3: Companion and Competitor (2001) fell back to 703 pages. Now Volume 4 (dated 2009), but published by Yale University Press rather than Doubleday, the publisher of the first three volumes, keeps the page total respectable. Volume 5 is promised to deal with ‘the riddle-speech of Jesus’ parables … of Jesus’ self-designations … and the ultimate riddle of Jesus’ death’.